A review of the Pachyprotasis pallidistigma species group (Hymenoptera: Tenthredinidae) from China, with descriptions of three new species - Zhong, Yihai; Wei, Meicai (Zootaxa, 2012)
The Chinese species of the Pachyprotasis pallidistigma group are revised and a key to the world species of the group isprovided. Three new species of the group from China are described: P. bilineata sp. nov. (Yunnan), P. sichuanensis sp. nov. (Sichuan), P. shennongjiai sp. nov. (Hubei). The previously known species of the group are revised.